2009
DOI: 10.1177/0961203309103048
|View full text |Cite
|
Sign up to set email alerts
|

Isolated elevation of IgA anti-β2glycoprotein I antibodies with manifestations of antiphospholipid syndrome: a case series of five patients

Abstract: Current diagnostic classification criteria recommend elevated titres of anti-cardiolipin (aCL) and/or anti-beta(2)GPI antibody by ELISA IgG or IgM and/or lupus anticoagulant (LA) to confirm antiphospholipid syndrome (APS). Although IgA aPL antibodies have been shown to be pathogenic in animal models of APS, their clinical significance has remained elusive. We report four cases of exclusive IgA anti-beta(2)GPI antibody sero-positivity with concomitant clinical manifestations associated with APS. Four of the fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 14 publications
1
33
0
Order By: Relevance
“…A study by Lee SR et al showed that in sub-group of women with intra-uterine fetal demise and unexplained miscarriages who were previously negative for aPL antibodies, IgA anti-β2GPI was most commonly found [15]. Similar findings have been reported in case series of five patients with isolated elevation of IgA anti-β2GPI antibodies and history of unexplained recurrent abortion, intrauterine fetal death or preterm delivery because of pre-eclampsia [2]. Similarly, in a group of 36 women with unexplained recurrent abortions and negative for IgG anti-β2 GPI, the presence of isolated IgA-β2GPI was found in nearly 14% of these women [6].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…A study by Lee SR et al showed that in sub-group of women with intra-uterine fetal demise and unexplained miscarriages who were previously negative for aPL antibodies, IgA anti-β2GPI was most commonly found [15]. Similar findings have been reported in case series of five patients with isolated elevation of IgA anti-β2GPI antibodies and history of unexplained recurrent abortion, intrauterine fetal death or preterm delivery because of pre-eclampsia [2]. Similarly, in a group of 36 women with unexplained recurrent abortions and negative for IgG anti-β2 GPI, the presence of isolated IgA-β2GPI was found in nearly 14% of these women [6].…”
Section: Discussionsupporting
confidence: 56%
“…Other conditions have also been described, such as unexplained recurrent spontaneous abortion/pregnancy loss, acute cerebral ischemia, cognitive dysfunction or transient ischemic attack [2]. IgA antiphospholipid antibodies are not currently recognized as formal laboratory criteria for antiphospholipid syndrome (APS), but according to the last international consensus guidelines on antiphospholipid antibodies (aPL), testing for IgA isotype is recommended for both anticardiolipin antibodies (aCL) and anti- β 2GPI when results of conventional markers (IgG and/or IgM isotypes) are negative and APS is still suspected [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, IgA aB2GPI antibodies have gained clinical relevance and were recently included as a clinic classification criterion for systemic lupus erythematosus [17]. Likewise, determination of IgA aB2GPI antibodies is recommended in patients with snAPS [21], LES, and in ethnics groups with a high prevalence of IgA isotype antibodies such as African Americans and long lasting SLE patients [18, 22]. …”
Section: Introductionmentioning
confidence: 99%
“…IgA anti-␤2GPI antibodies are frequently detected in specific ethnic groups such as African Americans (22 ). Case reports have been published of exclusive IgA anti-␤2GPI seropositivity with concomitant clinical manifestations (71 ).…”
Section: Apas Measured By Elisamentioning
confidence: 99%